2020
DOI: 10.2147/prbm.s259563
|View full text |Cite
|
Sign up to set email alerts
|

<p>Psychological Distress and Signs of Post-Traumatic Stress in Response to the COVID-19 Health Emergency in a Mexican Sample</p>

Abstract: Objective: This study aimed to evaluate the psychological impacts of COVID-19 prevention measures, such as social isolation, on a Mexican sample. Methods: We conducted an online sociodemographic and Impact of Event Scale-Revised (IES-R) survey during the second phase of the COVID-19 outbreak in Mexico to evaluate the presence of psychological distress, signs of post-traumatic stress, and to identify the groups at highest risk in the sample. Results: Prevalence of psychological distress at moderate or severe le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 22 publications
6
56
1
11
Order By: Relevance
“…In the current review, different types of risk factors have been identified which might be correlated with the psychological impacts of COVID-19 among health care workers have been identified which includes sociodemographic factors (age, gender, ethnicity, marital status, occupation). 9 , 10 , 12 , 17 , 19 21 , 25 , 28 , 29 , 31 This is similar to the study of Germany, 3 Mexico, 38 the United Kingdom, 28 and a finding of China, 12 Luo et al 39 and different from the study of China. 27 …”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In the current review, different types of risk factors have been identified which might be correlated with the psychological impacts of COVID-19 among health care workers have been identified which includes sociodemographic factors (age, gender, ethnicity, marital status, occupation). 9 , 10 , 12 , 17 , 19 21 , 25 , 28 , 29 , 31 This is similar to the study of Germany, 3 Mexico, 38 the United Kingdom, 28 and a finding of China, 12 Luo et al 39 and different from the study of China. 27 …”
Section: Discussionsupporting
confidence: 67%
“…In the elderly populations, the magnitudes of anxiety, depression, and stress were found to be high as compared to younger ages, 10 , 17 , 20 , 21 , 25 , 31 which is consistent with the study of Asia and Europe 40 and inconsistent with the study of Mexico in which the psychological distress was prevalent in younger ages. 38 This might be due to the impact of the comorbidities, immune system capacity, and poor coping strategies elders experience with aging. Gender was another factor shown to have an association with common psychological conditions among HCW.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above, due to the fact that the sampling was non-probabilistic, there could be problems regarding the sample distribution, since, in the present study, most respondents were single women, from the center of the country, and with a high educational level. However, it suffices to review the sample distribution and characteristics of the participants in current research on to see that these data are consistent in various parts of the world, with women's responses ranging from 52% to 80% (Dai et al, 2020;González Ramírez et al, 2020;Muñiz & Corduneanu, 2020;Orellana & Orellana, 2020;Shacham et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…En el caso de los síntomas depresivos, estos aumentaron de 15% a 28% (Priego-Parra et al, 2020). Por su parte, González- Ramírez et al (2020) identificaron que el 27.7% de su muestra presentó síntomas de Estrés Postraumático durante la segunda fase de la COVID-19 en México. Adicionalmente encontraron que 22% presentó pensamientos intrusivos, 22.3% síntomas evitativos, y 12.2% hiperactivación.…”
Section: Introductionunclassified